PERSEPSI MAHASISWA TENTANG PERAN MEMBACA DALAM PEMBENTUKAN KEMAMPUAN LITERASI KRITIS - Khairani, Zuraida; Hayati, Najmi; Chan, Dwi Mutia (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to describe students' perceptions of the role of reading in developing critical literacy skills in the context of higher education. The research background stems from the phenomenon of low in-depth reading practices in the digital era, which is characterized by a culture of short reading and instant information consumption. The study used a qualitative approach with a descriptive design, involving 33 first-semester students selected through purposive sampling techniques. Data were obtained through open-ended questionnaires, semi-structured interviews, and documentation, then analyzed using the Miles and Huberman technique, which includes data reduction, data presentation, and conclusion drawing. The results show that students have a positive perception of the importance of reading as a means of developing analytical, evaluative, and reflective skills. However, students' reading practices are still superficial because they are more oriented towards completing academic assignments than developing in-depth understanding. The study also identified various obstacles to the implementation of critical reading, including internal factors such as low motivation, shallow reading habits, and limited reading skills, as well as external factors such as less dialogic learning designs, high workloads, and digital distractions.